Clinical evaluation of the eye-to-visual-pathway integrity of glaucomatous neurodegeneration using 1.5T MR imaging: The integrity of glaucomatous neurodegeneration - Engin, Kaya N; Yiğit, Ulviye; Bayramoğlu, Sibel Töreyen; Güner, Nurten Turan; Özyurt, Onur; Tufan, Kutlay; Ağaçhan, Ahmet; Çağatay, Penbe (International Journal of Clinical and Experimental Ophthalmology, 2022)
Aim: Accumulating data imply that glaucoma may represent a neurodegenerative disorder affecting the entire visual system. We evaluated retrobulbar glaucomatous damage with favorable techniques for 1.5T diffusion-tensor magnetic resonance imaging and we compared those techniques with clinical data in a large case series. Material and methods: This Cross-sectional study included 130 eyes of 65 patients with primary open-angle glaucoma. Patients with no known ocular or systemic concomitant disorders, neurological diseases, previous glaucoma surgeries, or antioxidant usage were selected. A decrease in thickness and deterioration in the optic nerve diffusion of severely glaucomatous eyes of patients with asymmetrical involvement was observed in optic nerve tractography. Optical coherence tomography and visual field results of the subjects were recorded. Glaucoma analysis with optical coherence tomography and standard automated perimetry results of the subjects were recorded. Diffusion-tensor magnetic resonance imaging analysis of optic nerves and radiations were performed, computing fractional anisotropy, apparent diffusion coefficient, axial diffusivity, and radial diffusivity. Correlation between the diffusion-tensor magnetic resonance imaging and clinical eye parameters of glaucomatous neurodegeneration were statistically evaluated. Results: The correlations between diffusion parameters and age were highly significant. Statistically significant correlations were found between ganglion cell complex and apparent diffusion coefficient, axial and radial diffusivities of optic nerves. Conclusion: Eye-brain connection in glaucoma can be evaluated with routine clinical instruments. Our study also revealed a limited correlation of retrobulbar glaucomatous neurodegeneration with ophthalmic damage. A better understanding of retrobulbar damage will enable us to develop more efficient strategies and a more accurate understanding of glaucoma.